Mo-modified MnOx for the efficient oxidation of high-concentration glucose to formic acid in water - Guo, Haixin; Li, Jialu; Xu, Siyu; Yang, Jirui; Chong, Gun Hean; Shen, Feng (Elsevier, 2023)
Severe Mo-modified MnOx binary oxide catalysts were synthesized and served as highly active catalysts for the oxidation of glucose to formic acid in water. A maximum formic acid yield of 79% was achieved from glucose (10 g/L) over Mo(1)-MnOx at 160 ◦C after 90 min of reaction time. Even when the initial glucose concentration was 110 g/L, 54% of formic acid yield could be obtained with Mo(1)-MnOx, which was almost twice the yield obtained with pristine MnOx as the catalyst. Characterization results showed that the low valence Mn (Mn2+ and Mn3+) ions were the active sites and played key roles in the oxidation of glucose to formic acid. The introduction of Mo could increase the content of low valence Mn (Mn2+ and Mn3+) ions and the adsorbed oxygen (Oads) ratio. A mechanism study indicated that arabinose and glyoxylic acid were the dominant intermediates. Various carbohydrates (xylose, fructose, maltose, sucrose, cellobiose) with high initial concentration afforded formic acid yields >45% demonstrating the potential of Mo(1)-MnOx for transforming lignocellulosic biomass to formic acid.